INFLUENCE OF pH ON UPTAKE AND BIOACCUMULATION OF RADIOCESIUM ( 137Cs) IN THE GREEN MUSSELS PERNA VIRIDIS - Mashiatullah, A.; Khan, M. S.; Javed, T.; Chaudhary, M. Z.; Qureshi, R. M.; Chughtai, F. (The Nucleus, 2010)
Radiotracer experiment was conducted to assess the influence of pH on uptake rate and bioaccumulation of 137Cs from dissolved phase in soft parts of green mussels (Perna viridis) collected from Karachi Coast, under controlled laboratory condition. Green mussels of size 5–7 cm were subjected to radiocesium activity of 24 KBq L-1 under three pH levels i.e., 7.5, 8 and 8.5. The uptake of 137Cs was monitored for a period of seven days. The results showed that uptake and bioaccumulation of 137Cs in mussels was dependent on pH levels. Higher bioaccumulation factors and uptake rates were found at pH 8.